Estudio de factibilidad para desarrollo e implementación de una Página Web para gestionar el proceso de ventas del Comercial Rodríguez en la ciudad de Babahoyo - Escudero Briones, Ronald Alexander (2021)
An analysis was carried out for the development and implementation of a web page to manage the sales of the commercial Rodríguez in the city of Babahoyo, with the application of surveys and interviews carried out with the manager and workers of the establishment that allowed to verify the processes at the time of generating a sale of gas for domestic use. Through the feasibility analysis it was found that: in the technique the existing equipment of the commercial was studied and what are the necessary improvements for the execution of the application, in the economic one there will be relevant gains after three years from its implementation and in the operation the information is given that the administrator as well as his secretary are in charge of manipulating the relevant data.